19 low mass hypervelocity star candidates from the first data release of the LAMOST survey. (August 2015) - Li, Yin-Bi; Luo, A-Li; Zhao, Gang; Lu, You-Jun; Wei, Peng; Du, Bing; Li, Xiang; Zhao, Yong-Heng; Han, Zhan-Wen; Wang, Bo; Wu, Yue; Zhang, Yong; et al.
Abstract Hypervelocity stars are believed to be ejected out from the Galactic center through dynamical interactions between (binary) stars and the central supermassive black hole(s). In this paper, we report 19 low mass F/G/K type hypervelocity star candidates from over one million stars found in the first data release of the LAMOST regular survey. We determine the unbound probability for each candidate using a Monte-Carlo simulation by assuming a non-Gaussian proper-motion error distribution, and Gaussian heliocentric distance and radial velocity error distributions. The simulation results show that all the candidates have unbound possibilities over 50% as expected, and one of them may even exceed escape velocity with over 90% probability. In addition, we compare the metallicities of our candidates with the metallicity distribution functions of the Galactic bulge, disk, halo and globular clusters, and conclude that the Galactic bulge or disk is likely the birth place for our candidates.